Impact of Zinc and/or Herbal Mixture on Ruminal Fermentation, Microbiota, and Histopathology in Lambs - Petrič, Daniel; Mravčáková, Dominika; Kucková, Katarína; Kišidayová, Svetlana; Cieslak, Adam; Szumacher-Strabel, Malgorzata; Huang, Haihao; Kolodziejski, Pawel; Lukomska, Anna; Slusarczyk, Sylwester; Čobanová, Klaudia; Váradyová, Zora (Frontiers in Veterinary Science, 2021)
We investigated the effect of diets containing organic zinc and a mixture of medicinal herbs on ruminal microbial fermentation and histopathology in lambs. Twenty-eight lambs were divided into four groups: unsupplemented animals (Control), animals supplemented with organic zinc (Zn, 70 mg Zn/kg diet), animals supplemented with a mixture of dry medicinal herbs (Herbs, 100 g dry matter (DM)/d) and animals supplemented with both zinc and herbs (Zn+Herbs). Each lamb was fed a basal diet composed of meadow hay (700 g DM/d) and barley (300 g DM/d). The herbs Fumaria officinalis L. (FO), Malva sylvestris L. (MS), Artemisia absinthium L. (AA) and Matricaria chamomilla L. (MC) were mixed in equal proportions. The lambs were slaughtered after 70 d. The ruminal contents were used to determine the parameters of fermentation in vitro and in vivo and to quantify the microbes by molecular and microscopic methods. Samples of fresh ruminal tissue were used for histopathological evaluation. Quantitative analyses of the bioactive compounds in FO, MS, AA, and MC identified 3.961, 0.654, 6.482, and 12.084 g/kg DM phenolic acids and 12.211, 6.479, 0.349, and 2.442 g/kg DM flavonoids, respectively. The alkaloid content in FO was 6.015 g/kg DM. The diets affected the levels of total gas, methane and n-butyrate in vitro (P < 0.046, < 0.001, and < 0.001, respectively). Relative quantification by real-time PCR indicated a lower total ruminal bacterial population in the lambs in the Zn and Zn+Herbs groups than the Control group (P < 0.05). The relative abundances of Ruminococcus albus, R. flavefaciens, Streptococcus bovis, and Butyrivibrio proteoclasticus shifted in the Zn group. Morphological observation found a focally mixed infiltration of inflammatory cells in the lamina propria of the rumen in the Zn+Herbs group. The effect of the organic zinc and the herbal mixture on the parameters of ruminal fermentation in vitro was not confirmed in vivo, perhaps because the ruminal microbiota of the lambs adapted to the zinc-supplemented diets. Long-term supplementation of a diet combining zinc and medicinal herbs, however, may negatively affect the health of the ruminal epithelium of lambs.